Very High Prevalence of Frozen Shoulder in Patients With Type 1 Diabetes of ≥45 Years' Duration: The Dialong Shoulder Study - Juel, Niels Gunnar; Brox, Jens Ivar; Brunborg, Cathrine; Holte, Kristine Bech; Berg, Tore Julsrud (Archives of physical medicine and rehabilitation, 2017)
To compare the prevalence of shoulder disorders and self-reported shoulder disability in patients with long-term type 1 diabetes mellitus and diabetes-free subjects; and to explore the association between the long-term glycemic burden and shoulder disability in the diabetes group. Cross-sectional study of shoulder diagnoses with 30 years' historical data on glycemic burden in patients with diabetes. Diabetics center and a university hospital. Subjects attending the Norwegian Diabetics Center in 2015 with type 1 diabetes since 1970 or earlier were eligible (N=136). One hundred and five patients were included, and 102 (50% women; mean age, 61.9y) completed the study together with 73 diabetes-free subjects (55% women; mean age, 62.5y). Not applicable. Shoulder diagnoses decided through clinical examination according to scientific diagnostic criteria. Frozen shoulder was diagnosed in 60 (59%) patients with diabetes and 0 diabetes-free subjects, with a lifetime prevalence of 76% in the diabetes group versus 14% in the diabetes-free subjects. Patients with diabetes had higher disability and higher mean QuickDASH scores (23.0±19.9) than diabetes-free subjects (8.9±12.0), with a mean difference of −14.2 (95% confidence interval, −19.3 to −9.0) points (P<.001). We found an association between chronic hyperglycemia and QuickDASH scores, with a 6.16-point increase in QuickDASH scores per unit increase in glycated hemoglobin A1c (HbA1c) (P=.014). The point prevalence of frozen shoulder in patients with long-lasting type 1 diabetes was 59%, and the lifetime prevalence was 76%. The diabetes group had more shoulder disability than diabetes-free subjects. The historical HbA1c level was associated with increased shoulder disability. •Of patients with type 1 diabetes for ≥45 years, 59% had frozen shoulder, with 73% affected bilaterally.•Patients with painful frozen shoulder had highest disability and least shoulder mobility.•High glycemic index was associated with severe disability and restricted shoulder mobility.